Histologic evaluation of bone healing following low level laser irradiation (experimental study) - Kashmola, Muhanad Ali Hamdon; Mustafa, Nazih Shaban; Al Hussayni, Ali Hussien (ELSEVIER, 2015)
The aim of the present study is to evaluate the effect of low level laser irradiation on zygomatic bone healing in rabbit. A hole was made using a surgical bur in zygomatic bone of rabbit and a low energy laser was applied on bone of experimental group and compared to control non- irra- diated group. This study showed that application of low-energy laser has a promoting effect and facilitate bone deposition in the bony defect of the experimental group when compared to control group. Application of low-energy laser have pro- moting effect on acceleration of bone healing.